Aktivitas Antibakteri Sabun Organik Berbasis Ekstrak Kopi Robusta (Coffea canephora) Terhadap Escherichia coli ATCC 8739 - Fatimah Fatimah; Maya Istyadji; Yudha Irhasyuarna Fatimah (Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2026)
The purpose of this study was to determine the effectiveness of robusta coffee extract-based organic soap (Coffea canephora) against the growth of Escherichia coli ATCC 8739 bacteria. This study used a completely randomized design (CRD) with seven treatment groups of robusta coffee soap at concentrations of 10%, 25%, 50%, 75%, 100%, 150%, and 300%, a positive control (ampicillin), and a negative control (aquadest). The disc diffusion method was used to evaluate antibacterial activity. Data were analyzed using one-way ANOVA and Tukey's post-hoc test. The results showed that the inhibition zone diameter increased with increasing concentration of robusta coffee extract against E. coli. At concentrations ≥150%, the inhibition zone was equivalent to or greater than the positive control ampicillin, with significant differences (p < 0.05). These results suggest that robusta coffee soap has potential as an environmentally friendly natural antibacterial alternative and can promote the use of local robusta coffee.